THE EFFECTIVE VOLUME OF WATER IN SEVERAL TYPES OF SOIL FOR THE GROWTH OF Mucuna bracteata - Pauliz Dwi Hastuti; Sri Manu Rohmiyati; Ashabul Kahfi (Jurnal Agrivet, 2018)
The aim of this research was to determine the effective volume of water in several types of soil for the growth of Mucuna bracteata. This research was conducted at the Education and Research Garden (KP-2) of the Stiper Agricultural Institute located in Maguwoharjo, Sleman, DIY. This study uses factorial experiments arranged in Completely Randomized Design (CRD) consisting of two factors and five replications. The first factor was the volume of water spray/day/plant consisting of four volume levels, namely: 50 ml, 100 ml, 150 ml and 200 ml. The second factor was the type of soil consisting of three types of soil, namely : regosol, latosol and grumusol. The results of the research data were analyzed using variance (Analysis of variance) at a real level of 5%. Data that is significantly different is continued with Duncan's multiple distance test or DMRT (Duncan multiple range test) at a real level of 5%. The results showed that there was no good combination of the volume of water and soil type on the growth of Mucuna bracteata. The volume of 50 ml / plant water was sufficient to produce good Mucuna bracteata plant growth. Mucuna bracteata plants can grow in regosol, latosol, and grumusol soil types.Keywords: volume, water, soil type, Mucuna bracteata